TRENDS OF DEVELOPMENT OF MARKETING SALES AND COMMUNICATION POLICY OF DOMESTIC AND FOREIGN BANKS UNDER CONDITIONS OF DIGITAL ECONOMY - DEMKO, M.; HRYNIV, N. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In market conditions, economic instability forces commercial banks to seek a variety of marketing tools of influence customer behavior within individual components of their marketing mix. It is determined that today domestic banks focus on foreign experience in the application of sales systems and promotion of banking products, which is due to their desire to save costs, development of scientific and technological progress, reducing the free time of customers. It is established that of all the variety of modern tools that have become widespread both in domestic practice and abroad are mobile banking and Internet banking. The results of the study show that among Ukrainian banks, whose Internet banking services are most used by customers, the priority belongs to JSC CB «Privatbank». In the field of mobile banking, the leaders are JSC CB «Privatbank» and JSC «ALFA-BANK». The Conducted analysis of sales channels and promotion of banks on the example of the United States showed that the advantage of customers there is given to online and mobile channels compared to ATMs, branches or telephones. However, when commercial banks use remote product sales channels, it is important for them to establish two-way communication with customers in the framework of direct marketing using e-mail, telephone or website. This indicates the growing role of such a component in the system of integrated marketing communications of banking institutions as direct marketing. At the same time, when choosing of the mobile banking system or Internet banking of a certain commercial bank, customers focus on loyalty to him it, the image of the bank. Therefore, the system of marketing communications of a banking institution should be focused on their formation using its various components. At the same time, the experience functioning of competing banks under conditions of digital economy should be taken into account.
Keywords: Internet banking; mobile banking; direct marketing as a form of informing customers; digital economy; integrated marketing communications